-0.4=(g/3)-0.

Simple and best practice solution for -0.4=(g/3)-0. equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -0.4=(g/3)-0. equation:



-0.4=(g/3)-0.
We move all terms to the left:
-0.4-((g/3)-0.)=0
We add all the numbers together, and all the variables
-((+g/3)-0.)-0.4=0
We multiply all the terms by the denominator
-((+g-(0.4)*3)-0.)=0
We calculate terms in parentheses: -((+g-(0.4)*3)-0.), so:
(+g-(0.4)*3)-0.
We add all the numbers together, and all the variables
(+g-(0.4)*3)
We calculate terms in parentheses: +(+g-(0.4)*3), so:
+g-(0.4)*3
determiningTheFunctionDomain g-(0.4)*3
We add all the numbers together, and all the variables
g-1.2
Back to the equation:
+(g-1.2)
We get rid of parentheses
g-1.2
Back to the equation:
-(g-1.2)
We get rid of parentheses
-g+1.2=0
We add all the numbers together, and all the variables
-1g+1.2=0
We move all terms containing g to the left, all other terms to the right
-g=-1.2
g=-1.2/-1
g=1+0.2/1

See similar equations:

| −0.03x^2−0.6x+0.5=0 | | w-4.2=1.93 | | 6x^2+2x-54=2x | | 2x+10+5x+3=90 | | 7x+40=x3x+112 | | y+1.3=9.79 | | −0.03x2−0.6x+0.5=0-0.03x2-0.6x+0.5=0 | | 3x+4+38=0 | | 4b+5.2=10.8 | | 3(36)-y=5y | | 2=25x+0.2 | | 4x+8x+12=180 | | (2-x)3=12 | | 17-2v=15 | | 8x+4=12x+6 | | 4+x7=10 | | -3u+8(u+4)=12 | | 8t-30=6t | | -39=-8y+5(y-3) | | -36=8(x+3)+4x | | 48=6(x+3) | | 4x=69=30+ | | 20+3x=8+ | | 9n-11=10n-3 | | -0.5x+7=8 | | Z=6.2+37i | | 5x-2*x-10+3=8 | | Z=-91+14.6i | | H=5+18t+16t^2 | | 5v-14=4v | | s-3(7)+48=2s+7 | | N2+24=10n |

Equations solver categories